A planning study for evaluation of feasibility and benefit of generalized equivalent uniform dose-assisted optimization in volumetric-modulated arc therapy for recurrent head and neck cancer - Lee, Chou-Hsien; Jhang, Zih-Ruei; Yeh, Shyh-An; Chen, Yi-Ling (Therapeutic Radiology and Oncology, 2018)
Background: Re-irradiation is effective but challenging on balancing the tumor control and late complications for recurrent head and neck cancer (HNC). The aim of this study was to investigate the feasibility of incorporating the biologically based generalized equivalent uniform dose (gEUD) objective function in the volumetric-modulated arc therapy (VMAT) treatment planning optimization process and to evaluate its benefit in such a clinical dilemma. Methods: Five recurrent HNC cases were selected. Respective original VMAT plan which fulfilled acceptable constraints was created using dose-volume (DV) optimization for each case in the first phase. Based on the DV plan, multiple corresponding plans incorporating the added single Max EUD objective for the spinal cord (SC) with stepwise stricter constraint for further biological optimization were generated for dosimetric comparison. Evaluated parameters compared between DV and DV-gEUD plans included target coverage, conformity index, homogeneity index, and sparing of organs at risk (OARs). Results: When adopting SC_gEUD90% and SC_gEUD80% as Max EUD constraint of SC, DV-gEUD optimization compared to DV optimization yielded 17.1% and 20.3%, reduction of the average Dmax of SC, respectively (both P value